Atividade Florestal e o Desenvolvimento Socioeconômico em Três Lagoas e Região: Uma Análise Baseada na Abordagem de Cluster - Sirlei Tonello Tisott (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
The cluster of pulp and paper in Três Lagoas-MS, although in the embryonic stage, it is important for development, causing quantitative changes and conditions that enhance the prosperity and development in the region, given that forestry activity has become one of the best alternatives for the region's economic growth. The aim of this paper is to analyze the importance and effects of forestry activity for the labor market and the local and regional economy of Três Lagoas-MS. This context was explored from secondary and primary data, using the mixed method research, with qualitative and quantitative data. The results show that forestry activity was important for the labor market and the economy of Três Lagoas and the region, contributing to the opening of new enterprises and improvement of existing businesses. There was also a quantitative and qualitative change in the local labor market, with increased jobs, increased income, increased average salary and intensification of training and qualification programs of people for the labor market, demonstrating growth and development in this aspect. It is verified that forestry activity is important for local, regional and state economy, and it has boosted entrepreneurship and generated positive effects on the labor market, however, it alerts to the region's vulnerability due to its dependence as a prevailing activity, which it keeps many jobs and businesses settled in the city to serve, direct or indirectly, the forestry activity.